NORM INCONSISTENCY TO EXAMINE THE BANKRUPTCY CASE IN SHARIA ECONOMIC FIELD IN THE PERSPECTIVE OF LEGAL POLICY OF ISLAMIC AND COMMERCIAL COURT ESTABLISHMENT - Hari Purwadi, Adhiputro Pangarso Wicaksono, Adi Sulistiyono (International Journal of Advanced Science and Technology, 2020)
This research aimed to find out the correlation between the norm inconsistency of authority to examine the bankruptcy case in sharia economic field and the legal policy of Islamic and Commercial Court establishment. The research method was normative method with statute and historical approaches. The result of research showed that the difference of legal policy in the establishment of Islamic and Commercial Courts cause norm inconsistency of absolute authority. Legal policy of Islamic Court establishment aims to create an official institution to Muslim community to settle the dispute in litigation way, it is because Islamic court has been existent non-formally before Indonesia was born. Meanwhile, the establishment of Commercial Court is intended to meet the need for the fair, quick, transparent, and effective resolution of debt-loan conflict related to bankruptcy and newly created as the response to monetary crisis in 1997. The norm inconsistence should be removed by expanding the absolute competency of Islamic Court to examine the bankruptcy case in sharia-economic field and to establish Islamic Commercial Court institution as the court that specifically authorized to examine the bankruptcy case in Sharia-economic field.